Habitus of Journalists: An Analysis of the Behavior in Utilizing Artificial Intelligence - Krisdianto, Bayu Murti; Gumilar, Gumgum (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2026)
Background: Developments in artificial intelligence (AI) models have transformed how journalists work on a daily basis. AI has been adopted by both international and national media, including print, television, radio, and online, at both the editorial and individual levels. Purpose: This study aims to explore how journalists in Bandung choose and utilize AI to support news production. Methods: This research used a qualitative method with a case study approach. Data collection was conducted through structured interviews with journalists in Bandung, selected using snowball sampling. Data analysis techniques used interactive analysis by Miles and Huberman, along with member checking for data validation. Results: All interviewed journalists use and benefit from AI tools in their journalistic activities. The most commonly used applications are ChatGPT, Gemini, Perplexity, and Pinpoint. AI is mainly used for interview transcription, translation, data searching, brainstorming, data validation, creating captions, and generating interesting headlines. The use of AI simplifies and streamlines work in terms of time, thus making work more effective. Conclusion: Journalists in Bandung actively choose and utilize AI to accelerate their work. The use of AI is allowed as long as journalistic ethics are observed. Implications: Journalists should be more aware of data security when using AI and continue to improve their journalistic skills, rather than relying on AI to replace them.